Undifferentiated embryonic cell transcription factor 1 (UTF1) and deleted in azoospermia‐like (DAZL) expression in the testes of donkeys. (20th January 2017) - Lee, YS; Jung, HJ; Yoon, MJ
Contents: Putative markers for each specific germ cell stage can be a useful tool to study the fate and functions of these cells. Undifferentiated embryonic cell transcription factor 1 (UTF1) is a putative marker for undifferentiated spermatogonia in humans, rats and horses. The deleted in azoospermia‐like (DAZL) protein is also expressed by differentiated spermatogonia and primary spermatocytes in several species. However, whether the expression patterns of these molecular markers are identical and applicable to donkeys remains to be elucidated. The objective of this study was to investigate the expression patterns of UTF1 and DAZL in donkey testicular tissue, using immunohistochemistry (IHC). Testicular samples were collected from routine field castration of donkeys in Korea. The reproductive stages (pre‐ or post‐puberty) of the testes were determined from the morphological characteristics of cross‐sections of the seminiferous tubules. For IHC, the UTF1 and DAZL primary antibodies were diluted at 1:100 and 1:200, respectively. The immunolabelling revealed that UTF1 was expressed in approximately 50% of spermatogonia in the pre‐pubertal stage, whereas its expression was limited to an early subset of spermatogonia in the post‐pubertal stage. DAZL was expressed in some, but not all, spermatogonia in the pre‐pubertal spermatogonia, and interestingly, its expression was also observed in spermatogonia and primary spermatocytes in the post‐pubertal stage. Co‐immunolabelling of the germ cells with both UTF1 and DAZL revealed three types of protein expression patterns at both reproductive stages, namely UTF1 only, DAZL only and both UTF1 and DAZL. These protein molecules were not expressed in Sertoli and Leydig cells. In conclusion, a co‐immunolabelling system with UTF1 and DAZL antibodies may be used to identify undifferentiated (UTF1 only), differentiating (UTF1 and DAZL), and differentiated spermatogonia (DAZL only) in donkey testes.